Fish Feeder for Aquaculture with Fish Feed Remaining and Feed Out Monitoring System Based on IoT - Ali Rizal; Gamma Aditya; Haidzar Nurdiansyah (Procedia of Engineering and Life Science, 2021)
Feeding fish is a process that affects fish yields. Undisciplined feeding of fish resulted in decreased quality and quantity of fish. The potential for this problem can be reduced by implementing an IoT-based technology. That technology needs to have a monitoring system for remaining feed and the success of feeding. This study using a proximity sensor and infrared distance sensor for the monitoring system for the fish feeder. The results obtained are that the infrared distance sensor can provide information about the remaining fish feed more accurately after being calibrated, the average percentage error of the total test is 5,1%. While the proximity infrared sensor can provide information on the success of throwing feed, from the total testing of the proximity sensor, the success rate of detecting throw feed is 100%. Both information can be monitored via the Blynk platform on the user’s smartphone.